Anatomic variations of the aortic arch depicted on 444 CT angiographies (2016)
With a view to describing the different anatomic variations of aortic arch branching, their prevalence, the demographic characteristics of the sample, and to propose a new classification for aortic arch branching patterns, 460 thoracic computed tomography angiographies (CTA) with 3D reconstruction were reviewed from January 2012 to December 2014. A total of 444 subjects were included in the study. Of those, 153 (34.4%) were male. Anatomic variations were found in 178 (40.1%) subjects. Prevalence by type of aortic arch (AA) branching pattern were found as follows: Type 1 or "Normal branching": Brachiocephalic trunk (BT), left common carotid artery (LCC), left subclavian artery (LS), in this order, was 59.9% (266/444 subjects); Type 2 or "Bovine arch": BT and LCC arising from the AA in a common trunk, was 27.9% (124/444 subjects); Type 3: LCC originating separately from the BT, was 9.9% (44/444 subjects); Type 4, left vertebral artery arising from the AA, was 2.2% (10/444 subjects).